Pengaruh Produk Domestik Regional Bruto Terhadap Pertumbuhan Ekonomi, Dan Tingkat Kemiskinan Di provinsi Jawa Timur Periode 2019-2023 - Nurul Lathifah; Muchamad Afif (Jurnal Ekonomi dan Bisnis Digital, 2025)
Poverty remains a major problem in various regions in Indonesia, including East Java. Although economic growth in East Java has shown improvement in recent years, poverty remains a serious problem and requires further attention to improve the welfare of the people in the region. This raises the question of whether Gross Regional Domestic Product (GRDP) is truly capable of increasing economic growth while reducing poverty levels. The purpose of this study is to analyze the effect of GRDP on economic growth and poverty levels in East Java for the period 2019–2023. The method used is quantitative research with secondary data from the Central Statistics Agency (BPS) as well as simple linear regression analysis, t-test, and coefficient of determination (R²). The results show that GRDP has a positive but insignificant effect on economic growth, and a negative but insignificant effect on poverty levels. Thus, an increase in GRDP has not been able to provide a real impact on reducing poverty levels or accelerating economic growth without the support of other factors such as equitable development, infrastructure quality, and local government policies. Based on the results of this study, it is recommended that local governments should not only focus on increasing GRDP, but also pay attention to equitable development, improving infrastructure quality, and economic policies that pay more attention to the interests of the community, so that economic growth can reduce poverty in a sustainable manner.